What are the key directions in the genetics of attention deficit hyperactivity disorder? - Martin, Neilson; McDougall, Megan; Hay, David (Lippincott Williams & Wilkins, 2008)
Purpose of review: The aim of this review is to describe the considerable advances in consolidating the empirical evidence on several key topics in the genetics of attention deficit hyperactivity disorder, namely the quantitative genetic studies of the nature of attention deficit hyperactivity disorder and its comorbidities, the molecular genetic studies that show modest but consistent effects of specific genotypes, and the growing recognition of genotype by environment interaction. Such interactions are studied to explain what happens when individuals with a susceptible genotype are exposed to a particular environment.Recent findings: There have been a significant number of twin studies that have examined different models of the symptomatology of attention deficit hyperactivity disorder and how these symptoms are reported. Similarly, molecular genetic research is complicated by very different outcome measures, and study across the whole field is made more problematic by genotype by environment interaction effects. One of the most interesting areas of development is that of psychopharmacogenetics.Summary: Two key developments have been integrative models of the genetics of attention deficit hyperactivity disorder and brain structure, which may have implications for future attention deficit hyperactivity disorder subtyping, and collaboration. This is not just within attention deficit hyperactivity disorder as in the IMAGE study, but also across disciplines.